EVOLUÇÃO DO RELEVO NA SERRA DO MAR NO ESTADO DE SÃO PAULO A PARTIR DE UMA CAPTURA FLUVIAL - Oliveira, Déborah de; Neto, José Pereira de Queiroz (GEOUSP Espaço e Tempo (Online), 2007)
Serra do Mar emerged by erosional processes of Santos fault line to the Upper Cretaceous, in the present continental south-american platform. Santos fault line caused abatement of the plateau, which corresponds at Japi erosional surface. The scarp’s retreat of Serra do Mar caused the river capture of plateau’s rivers as Guaratuba, in Boracéia-SP. Alto Guaratuba basin is located at Parque Estadual da Serra do Mar, near Serra do Mar scarp, approximately at 45º 56’ and 45º 52’ of longitude west and 23º 38’ and 23º 42’ of latitude south. Guaratuba river flows from NE-SW on the plateau to N-S on the scarp and its change suggests that Guaratuba is captured by headward erosion, as result of Serra do Mar’s regressive erosion. Some evidences are found: the elbow of capture in a sharp change from NE-SW to N-S, cutting rocks’ structural lines, near the scarp; a wind gap swampy and gravelly, near the elbow of capture, as an ancient Guaratuba’s riverbed; river profile of Guaratuba as a powerful slope rupture.